2020
DOI: 10.1101/2020.01.28.917278
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Functional characterization of clinical isolates of the opportunistic fungal pathogenAspergillus nidulans

Abstract: AbstractAspergillus nidulans is an opportunistic fungal pathogen in patients with immunodeficiency and virulence of A. nidulans isolates has mainly been studied in the context of the chronic granulomatous disease (CGD), with characterization of clinical isolates obtained from non-CGD patients remaining elusive. This study therefore carried out a detailed biological characterization of two A. nidulans Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“…To gain insights into A. nidulans pathogenicity, we sequenced 9 clinical isolates that were originally identified as A. nidulans from patients with various pulmonary diseases, including 2 isolates from CGD patients. Two of these isolates belong to A. nidulans and have been described in detail elsewhere [27]. However, our phenotypic and genomic analyses showed that 6 of the remaining 7 isolates are not A. nidulans but rather allodiploid hybrids of Aspergillus latus, a species that arose from allodiploid hybridization between Aspergillus spinulosporus and an unknown second parental species closely related to Aspergillus quadrilineatus (both from section Nidulantes).…”
Section: Introductionmentioning
confidence: 68%
“…To gain insights into A. nidulans pathogenicity, we sequenced 9 clinical isolates that were originally identified as A. nidulans from patients with various pulmonary diseases, including 2 isolates from CGD patients. Two of these isolates belong to A. nidulans and have been described in detail elsewhere [27]. However, our phenotypic and genomic analyses showed that 6 of the remaining 7 isolates are not A. nidulans but rather allodiploid hybrids of Aspergillus latus, a species that arose from allodiploid hybridization between Aspergillus spinulosporus and an unknown second parental species closely related to Aspergillus quadrilineatus (both from section Nidulantes).…”
Section: Introductionmentioning
confidence: 68%
“…nidulans (4.1 × 10 -11 ), which can be used, for instance, to more precisely date the divergence between two strains or the origin of clinical outbreaks. Other sequencing studies have shown that relationships between genome and phenotypic plasticity can be mapped by comparing genomes and phenotypes from different isolates ( Bastos et al. 2020 , Drott et al.…”
Section: Whole-genome Sequencing Applications In the Clinicmentioning
confidence: 99%
“…As more genomes from strains and species in section Fumigati become available, our power to detect quantitative differences will increase, and allow us to more robustly test the conserved pathogenicity model and expand our species-specific pathogenicity model to include "strainspecific" elements. This will be especially important considering the continued and growing appreciation for strain-specific traits and differences in Aspergillus genomes and pathogenicity (Keller 2017;Bastos et al 2020;Dos Santos et al 2020;Steenwyk, Lind, Ries, et al 2020;Kowalski et al 2021). Future studies will also place A. oerlinghausenensis, another species closely related to A. fumigatus (Houbraken et al 2016), within this evolutionary framework of pathogenicity, but due to our previous genome-wide phylogenomic analyses of A. oerlinghausenensis, A. fischeri, and A. fumigatus ), we do not anticipate that inclusion of A. oerlinghausenensis will drastically change our findings.…”
Section: Discussionmentioning
confidence: 99%